STRATEGIC MANAGEMENT OF DIGITAL GROWTH IN ENTERPRISES (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The modern stage of the global economy development is characterized by unprecedented intensity of digital transformation, fundamentally changing competitive landscapes, business models, and value creation mechanisms. In conditions of increasing global turbulence caused by pandemic challenges, geopolitical conflicts, and macroeconomic instability, the ability to effectively manage digital growth becomes a critical determinant of organizational survival and long-term competitiveness. This study addresses the problematic of strategic management of enterprise digital growth in conditions of market turbulence through development of an integrated conceptual model.The theoretical foundation of the proposed concept is based on synthesis of dynamic capabilities theory with digital business strategy theory by Bharadwaj A. and colleagues. This integration creates a holistic analytical framework explaining how organizations can systematically develop and maintain competitive advantages in conditions of digital turbulence. Dynamic capabilities in the context of digital transformation manifest through three interconnected categories: sensing capability (systematic scanning of technological horizon), seizing capability (rapid experimentation and scaling), and transforming capability (reconfiguration of organizational assets).The concept proposes viewing digital growth as a multidimensional process systematically integrating four interconnected dimensions: technological (integration of advanced digital technologies), organizational (transformation of management structures and processes), strategic (fundamental rethinking of business models), and cultural (formation of digital mindset and innovation culture). This multidimensional approach overcomes the fragmentary nature of existing models focusing predominantly on technological aspects.The integrated model of strategic management of digital growth consists of five interconnected levels: strategic goal-setting and positioning (long-term vision formation), architectural design (technological, organizational, and information architecture), portfolio management of initiatives (balanced portfolio of incremental, transformational, and experimental projects), operational implementation (agile teams and rapid scaling), and monitoring and adaptation (comprehensive metrics system and strategy adjustment). Each level of the model is based on corresponding theoretical concepts and empirical research ensuring theoretical validity and practical applicability.Human capital management constitutes a cross-cutting element of the concept penetrating all model levels. A three-level model of digital competencies development (basic, functional, strategic) and three-aspect model of digital culture formation (data-driven mindset, experimentation culture, collaboration culture) are proposed. Strategic management of digital growth in conditions of extreme turbulence requires specific approaches including adaptive strategic planning, strategic ambidexterity, and development of digital resilience. Integrated risk management encompasses four risk categories: technological, organizational, strategic, and regulatory.
Keywords: digital growth; strategic management; digital transformation; dynamic capabilities; market turbulence; digital strategy; digital maturity; organizational architecture; digital resilience